The determinants of capital structure of Portuguese firms - Teixeira, João (2019)
This paper investigates the determinants of capital structure based on a sample of 2,804 non-financial Portuguese firms, from 2000 to 2009. A standard capital structure model is estimated controlling for firm-specific and market factors commonly used in the literature. The model is further estimated for sub samples of firms based on size, growth opportunities and leverage, as well as for the time periods before and during the international financial crisis. The result show that firms’ capital structure decision seems to conform more with the pecking order theory, rather than with the tradeoff theory. This is also true for different groups of firms based on size, growth opportunities and leverage. Finally, the results suggest that firms have adjusted their leverage as the international 2008 crisis begun.